Comparison of the Transepicondylar Axis Measured Using Computed Tomography Before Primary Total Knee Arthroplasty and the Surgical Measurement - Taşdemir, Zeki; Bulut, Güven; Baysal, Özgür; Çevik, Hüseyin Bilgehan; Elmalı, Nurzat; ELMALI, NURZAT (My University, 2017)
Objective: The purpose of this study was to evaluate the consistency of the angle between the posterior condylar line (PCL) and the transepicondylar axis (TEA) measured during surgery (sTEA) with that of the clinical transepicondylar axis (cTEA) measured using computerized tomography (CT) before primary total knee arthroplasty (TKA). Methods: The records of patients who had undergone primary TKA between 2013 and 2105 and with a preoperative CT measurement of the knee were evaluated. During surgery, following the distal femoral incision, PCL and sTEA lines were drawn on the surface with a ruler and a pencil and recorded with a digital camera. The angle between the cTEA, or the line joining the most prominent points of the medial and lateral epicondyles, and the PCL was measured using a picture archiving communication system (PACS). Results: The study group consisted of 9 knees of 9 patients (1 male, 8 female; mean age: 67 years, range: 59–80 years). The photographs indicating the angle between the sTEA line and the PCL revealed external rotation in 9 knees (100%), with a mean angle of 2.67±1.41° (range: 1–6°). The preoperative axial CT images also demonstrated external rotation in 9 knees (100%), with a mean angle of 4.67±1.41° (range: 2–7°). Conclusion: There was a difference between the sTEA, which is used to determine the rotation of femoral component during TKA, and the cTEA measured preoperatively using CT. It is safe to use 1 of these 2 techniques to check the result of the other. In the future, measurements made using CT will be used to design personalized anatomical prostheses.